Peningkatan Keterampilan Generik Sains pada Materi Tata Surya melalui Pembelajaran Berbantuan Aplikasi Solar System Scope untuk Siswa SMP - Ika Mustika Sari; Syifa Fauzi Ahmad; Amsor Amsor (Journal of Teaching and Learning Physics, 2019)
In order to survive and improve self quality in higher levels of education and work, generic science skills are needed. Generic science skill is the skill that can be grown from science learning as a provision to pursue careers in a broader field. In this day and age, many things can be done by using devices, including physics learning. This study aims to find out the differences of generic science skills improvement between a class that apply solar system learning with a scientific approach assisted by Solar System Scope with a class that do not use Solar System Scope. The method used in this study was quasi-experiment with the control group pretest-posttest design. The sample consisted of 31 experimental class students and 31 control class students in the junior high school in Bandung. Both classes were given the multiple choice test. The results of data analysis showed an improvement in both classes with N-gain 45.9% in the experimental class and 22.8% in the control class. The conclusion of this study can be showed by Mann Whitney hypothesis test which produces z = -3.60. It shows that there is a significant differences of generic science skills improvement between both classes after the implementation of solar system learning assisted by Solar System Scope.